2014
DOI: 10.1007/s40140-014-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Volume Management and Resuscitation in Thoracic Surgery

Abstract: Lung injury following thoracic surgery is a major cause of morbidity and mortality. A consistent risk factor is excessive perioperative fluid administration, not only following pneumonectomy, but also after lesser lung resections and esophageal surgery. Recent insights into the pathophysiology of lung injury after thoracic surgery include the role of the endothelial glycocalyx, pulmonary endothelium, lung lymphatics, and right ventricular dysfunction. While a restrictive approach to fluid administration may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…When switching to OLV, SVV measurements may give false results due to fact that it is unlikely to expose one lung to a high tidal volume. 8 10 In the present study, fluid therapy was guided by SVV measurements in 48.9% of the patients. The initial variables of the mechanical ventilator were set to a tidal volume of 8 mL/kg and a PEEP of 4 cmH 2 O, and SVV was maintained below 13%.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…When switching to OLV, SVV measurements may give false results due to fact that it is unlikely to expose one lung to a high tidal volume. 8 10 In the present study, fluid therapy was guided by SVV measurements in 48.9% of the patients. The initial variables of the mechanical ventilator were set to a tidal volume of 8 mL/kg and a PEEP of 4 cmH 2 O, and SVV was maintained below 13%.…”
Section: Discussionmentioning
confidence: 83%
“…In their studies, Ashes and Slinger 10 and Chau and Slinger 15 suggested that positive fluid balance should not exceed 20 mL/kg within the first 24 h, and the use of crystalloids should be limited to 2 L during the operation and below 3 L within the first 24 h. The use of colloids should be kept lower in adults and only be reserved to replace blood loss. In addition, urine output should be maintained above 0.5 mL/kg/h in the absence of acute renal failure and the replacement of losses to the third compartment should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, giving thoracic surgery patients more than 3 liters of intravenous fluid in the first 24 hours increases the chance of an acute lung injury. Right now, a moderately cautious approach should be taken into consideration because it can prevent fluid overload and reduce the danger of organ hypoperfusion and acute renal injury [12] [13]. Some pneumonectomies now employ goal-directed fluid therapy (GDFT), which uses dynamic hemodynamic parameters to target fluid administration.…”
Section: Discussionmentioning
confidence: 99%
“…A targeted fluid administration strategy for thoracic surgery is an important aspect of reducing postoperative ALI while minimizing end-organ injury. 98 Practice has changed since the deleterious effects of liberal fluid administration in pneumonectomy were first documented. 99 Today, euvolemia is the primary goal of intraoperative fluid management in lung resection and esophagectomy surgery.…”
Section: Fluid Managementmentioning
confidence: 99%